2022
DOI: 10.1109/access.2022.3223101
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Denoising for Super-Resolution (UDSR) of Real-World Images

Abstract: Single Image Super-Resolution (SISR) using Convolutional Neural Networks (CNNs) for many applications in supervised manner has resulted in state-of-the-art results. Such supervised models achieve remarkable accuracy; albeit their poor generalization ability for real-world Low-Resolution (LR) images. Supervised training in many SR works involves synthetically generated LR images from its corresponding High-Resolution (HR) images. As the distribution of such LR observation is relatively different from that of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…In [45] suggested an unsupervised denoising framework for super-resolution UDSR that applies a distinct denoising network to Real-World Super-Resolution. Measurement of the performance of SR and denoising networks showed that the combination improves both.…”
Section: Machine Learning With Image Denoisingmentioning
confidence: 99%
“…In [45] suggested an unsupervised denoising framework for super-resolution UDSR that applies a distinct denoising network to Real-World Super-Resolution. Measurement of the performance of SR and denoising networks showed that the combination improves both.…”
Section: Machine Learning With Image Denoisingmentioning
confidence: 99%